Women in Energy Sector in Nigeria: A Survey of Gender and Leadership in the Workplace - Ogunmusire, Adebisi (Àgídìgbo: ABUAD Journal of the Humanities, 2023)
Studies have also shown that women account for a significantly smaller number of workforce in the industry; they constitute less than 22% of employee and just 5% of Boards of Directors (BOD) making the energy sector one of the least gender-diverse sectors in the economy, even thougha much direr female representation is assumed to exist in the technical and field roles. According to Solanke (2019), “although the industry has begun to appreciate the value of gender balance and how it impacts the populace,we need to see how the Nigerian Government is taking a more active role in trying to push gender balance as actively as it does local content policies.”There are various disadvantages to the low level of female participation in the industry. First, energy companies have smaller number of highly qualified candidates to choose from when filling positions, especially in the middle and higher ranks, because many talented women either never join the industry or drop out prematurely. Second, companies inevitably miss out on higher quality of teamwork, diversity of perspectives, and creativity in solving technical and business problems unlike others with larger percentages of female employees. Third, the industry’s relative lack of gender diversity, particularly in the senior ranks, hurts its reputation as a first career choice for women. Left unchecked, this can create a vicious circle that could lead to the industry finding it progressively difficult to recruit women across board.